1989
DOI: 10.1016/s0006-3495(89)82675-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoresis and orientation of F-actin in agarose gels

Abstract: F-Actin was electrophoresed on agarose gels. In the presence of 2 mM MgCl2 and above pH 8.5 F-actin entered 1% agarose; when the electric field was 2.1 V/cm and the pH was 8.8, F-actin migrated through a gel as a single band at a rate of 2.5 mm/h. Labeling of actin with fluorophores did not affect its rate of migration, but an increase in ionic strength slowed it down. After the electrophoresis actin was able to bind phalloidin and heavy meromyosin (HMM) and it activated Mg2+-dependent ATPase activity of HMM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Electrical current applied to actin filaments suspended in a solution-filled well located between two gold electrodes results in those actin filaments aligning parallel to the electric lines and bridging the intervening gap between electrodes [ 59 ]. Other studies similarly indicate that actin filaments possess the ability to align parallel and perpendicular to the electric field depending on the nature of the field [ 60 , 61 ]. It is also conceivable that electric or magnetic fields contribute to neural structure.…”
Section: Electric Signal Propagation By Actin Filamentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical current applied to actin filaments suspended in a solution-filled well located between two gold electrodes results in those actin filaments aligning parallel to the electric lines and bridging the intervening gap between electrodes [ 59 ]. Other studies similarly indicate that actin filaments possess the ability to align parallel and perpendicular to the electric field depending on the nature of the field [ 60 , 61 ]. It is also conceivable that electric or magnetic fields contribute to neural structure.…”
Section: Electric Signal Propagation By Actin Filamentsmentioning
confidence: 99%
“…Additionally, the aforementioned models lack a true memory of recent inputs and are therefore unable to process the current information within the context of the recently observed data. As such, these models are inadequate and inappropriate tools with which to study real neurons, in particular the highly dynamic behavior observed during synaptic activation and with neural plasticity [ 59 , 60 , 81 , 82 ]. While synapses in ANN vary slowly during the learning process, these synapses are assumed to be static after the learning phase is over.…”
Section: Dendritic Cytoskeleton Information Processing Modelmentioning
confidence: 99%
“…Therefore, an approach must be taken to orient solutions ofpurified actin for study in EPR experiments. Previously, investigators have oriented actin in strong magnetic fields (Torbet and Dickens, 1984), by the flow of actin solutions (Miki and Mihashi, 1977), by the flow of actin sols (Popp et al, 1987), and by the electrophoresis of actin in agarose gels (Borejdo and Ortega, 1989). In the present study, we have oriented actin solutions by flow and determined the orientational distribution of the spin labels rigidly bound to actin.…”
Section: Introductionmentioning
confidence: 99%